Survey of junior doctors' knowledge of the use of new guidelines in the management of diabetic ketoacidosis in adults. (March 2014) - Nalla, Preethi; Nukalapati, Lokesh; Gosrani, Deepan; Evans, Peter J
Abstract: Diabetic ketoacidosis (DKA) is a common medical emergency. In recent years a weight‐based, fixed‐rate intravenous insulin infusion regimen has replaced the conventional sliding scale regimen for effective management of DKA. These guidelines have come into effect from 2012 at a hospital in south east Wales. A survey was conducted to assess the junior doctors' (medical and surgical) knowledge of these guidelines as per trust protocol. The results of this survey clearly show that a significant number of doctors (35% of medical and 63% of surgical doctors) were not aware of these guidelines; 15% of medical and 22% of surgical doctors were not aware of the criteria for the diagnosis of DKA. Copyright © 2014 John Wiley & Sons. Practical Diabetes 2014; 31(2): 81–83